Combretastatins D-3 and D-4, new macrocyclic lactones from Getonia floribunda - Namphung Vongvanich (2018)
Chemical investigation of biologically active compounds of Getonia floribunda led to the isolation of two new macrocyclic lactones, combretastatins D-3 (1) and D-4 (2). The structures of these compounds were confirmed by spectroscopic analyses. Combretastatin D-3 (1) exhibited cytotoxicity towards the small-cell lung cancer cell line (NCI-H187, IC50 = 13.0 ± 0.2 μg/mL) but was inactive against KB, BC-1, and Vero cell lines. Combretastatin D-3 (1) showed weak antitubercular activity with a minimum inhibitory concentration (MIC) of 100.0 μg/mL, and was inactive towards the malarial parasite. Combretastatin D-4 (2) was inactive in all antitubercular, antiplasmodial, and cytotoxic assays.